1975
DOI: 10.1111/j.1365-2222.1975.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on interrelations between eosinophilia, serum IgE and tissue mast cells

Abstract: Summary In an examination of a variety of diseases associated with a peripheral blood eosinophilia it is evident that the eosinophilia is not necessarily accompanied by increased amounts of serum IgE. Tissue eosinophilia occurring with mast cell hyperplasia and usually increased amounts of JgE, indicate atopic allergy. It is considered that the eosinophilic granuloma of soft tissue (Kimura's disease) is an atopic disease and quite different from histiocytosis X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently, mast cell granules have been shown to contain an eosinophilic chemotactic factor and their relation to eosinophilic infiltration has been suggested (8-10). Takenaka et al (11) indicated an intimate relationship between the distribution of mast cells and the infiltration of eosinophils in Kimura's disease. However, while the frequency of IgE producing plasma cells and mast cells is extremely high in the lesions of this disease, the recent study of Ishikawa et al (7) failed to show any definite relationship between the number and distribution of mast cells and the infiltration of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mast cell granules have been shown to contain an eosinophilic chemotactic factor and their relation to eosinophilic infiltration has been suggested (8-10). Takenaka et al (11) indicated an intimate relationship between the distribution of mast cells and the infiltration of eosinophils in Kimura's disease. However, while the frequency of IgE producing plasma cells and mast cells is extremely high in the lesions of this disease, the recent study of Ishikawa et al (7) failed to show any definite relationship between the number and distribution of mast cells and the infiltration of eosinophils.…”
Section: Discussionmentioning
confidence: 99%